Manipulating nonlinear emission and cooperative effect of CdSe/ZnS quantum dots by coupling to a silver nanorod complex cavity - Nan, Fan (2014)
Colloidal semiconductor quantum dots have three-dimensional confined excitons with large optical oscillator strength and gain. The surface plasmons of metallic nanostructures offer an efficient tool to enhance exciton-exciton coupling and excitation energy transfer at appropriate geometric arrangement. Here, we report plasmon-mediated cooperative emissions of approximately one monolayer of ensemble CdSe/ZnS quantum dots coupled with silver nanorod complex cavities at room temperature. Power-dependent spectral shifting, narrowing, modulation, and amplification are demonstrated by adjusting longitudinal surface plasmon resonance of silver nanorods, reflectivity and phase shift of silver nanostructured film, and mode spacing of the complex cavity. The underlying physical mechanism of the nonlinear excitation energy transfer and nonlinear emissions are further investigated and discussed by using time-resolved photoluminescence and finite-difference time-domain numerical simulations. Our results suggest effective strategies to design active plasmonic complex cavities for cooperative emission nanodevices based on semiconductor quantum dots.